2017
DOI: 10.2136/sssaj2017.03.0075
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon and Nitrogen Fraction Accumulation with Long‐Term Biosolids Applications

Abstract: global sustainability depends on the recycling of organic wastes, containing carbon and plant nutrients, back into food production. Biosolids are capable of building total soil organic matter, but their ability to build stable organic C and n fractions is less well understood. The sequestration of stable soil C and replacement of energy-requiring commercial fertilizers both have implications for greenhouse gas mitigation. Our aim was to assess the effectiveness of biosolids amendments to store labile and stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In our study, long‐term (20‐yr) biosolids application increased SOC in the top 30 cm of soils in three agroecosystems in California. This finding is consistent with studies in other regions that have documented beneficial reuse of biosolids as a strategy to sequester C in soils in surface soils (Brown et al., 2011; Hamdi et al., 2019; Nicolás et al., 2014; Pan et al., 2017). There are number of factors that improve SOC in soils, including improvements in soil quality, agronomic productivity, and the enhancement in soil microbial diversity (Lal, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, long‐term (20‐yr) biosolids application increased SOC in the top 30 cm of soils in three agroecosystems in California. This finding is consistent with studies in other regions that have documented beneficial reuse of biosolids as a strategy to sequester C in soils in surface soils (Brown et al., 2011; Hamdi et al., 2019; Nicolás et al., 2014; Pan et al., 2017). There are number of factors that improve SOC in soils, including improvements in soil quality, agronomic productivity, and the enhancement in soil microbial diversity (Lal, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Although the benefits of biosolids application are evident in many agricultural soils, most studies sample only the top 30 cm or less of soil (Pan et al, 2017;Pitombo et al, 2015;Stewart et al, 2012;Tian et al, 2013Tian et al, , 2009. There have been relatively few soil C studies that have examined deep soil C, regardless of the management practice examined.…”
Section: Introductionmentioning
confidence: 99%
“…The close proximity offers opportunities for processed manure and biosolids to be imported into this fallow zone, which will reduce fertilizer nutrient requirements. This would also build up the low SOM levels as has been demonstrated in a long-term manure trials at Pendleton, OR (Machado, 2011) and biosolids trials near Okanogan, WA (Cogger et al, 2013;Pan et al, 2017b).…”
Section: Crop-fallow Zonementioning
confidence: 90%
“…The chemical forms of organic matter added and subsequent form can affect the long term soil C and N sequestration efficiency [293]. Wang et al [294] revealed that soil C is the principal energy source to soil microorganisms and enzymes whereas the soil C/N ratio influences their activity.…”
Section: Changes Of Carbon To Nitrogenmentioning
confidence: 99%